2003
DOI: 10.1161/01.hyp.0000062882.42265.88
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Stretch-Induced Apoptosis in Smooth Muscle Cells Is Mediated by β 1 -Integrin Signaling Pathways

Abstract: Abstract-Recently we demonstrated that mechanical stress induces apoptosis of vascular smooth muscle cells in vitro and in vein grafts (Mayr et al. FASEB J. 2000;15:261-270). The current study was designed to investigate molecular mechanisms of mechanical stretch-induced apoptosis. Smooth muscle cells cultivated on silicone elastomer plates precoated with collagen I, elastin, laminin, or Pronectin were subjected to cyclic mechanical stretch. Interestingly, in response to mechanical stress, the number of apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
101
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 53 publications
6
101
0
Order By: Relevance
“…This results in low, oscillating, or reversing shear stress, which in turn leads to atherosclerosis and vascular calcification 30, 31. VSMCs sense the disturbed wall shear stress and pressure distension caused by intravascular and interstitial fluid overload through membrane mechanoreceptors, and activate the signaling pathways such as small guanosine triphosphatase related to Ras A (RhoA)/Rho‐associated protein kinase, mitogen‐activated protein kinase, phosphatidylinositol‐3‐kinase/protein kinase B, and extracellular signal‐regulated kinase 32, 33, 34. These signaling pathways induce the proliferation, migration, apoptosis, and osteoblastic differentiation of VSMCs, and altered VSMCs play a major role in vascular calcification 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…This results in low, oscillating, or reversing shear stress, which in turn leads to atherosclerosis and vascular calcification 30, 31. VSMCs sense the disturbed wall shear stress and pressure distension caused by intravascular and interstitial fluid overload through membrane mechanoreceptors, and activate the signaling pathways such as small guanosine triphosphatase related to Ras A (RhoA)/Rho‐associated protein kinase, mitogen‐activated protein kinase, phosphatidylinositol‐3‐kinase/protein kinase B, and extracellular signal‐regulated kinase 32, 33, 34. These signaling pathways induce the proliferation, migration, apoptosis, and osteoblastic differentiation of VSMCs, and altered VSMCs play a major role in vascular calcification 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…In vascular smooth muscle cells, cyclic strain stimulated mitogenesis through integrin ␣ v ␤ 3 -dependent release of plateletderived growth factor (46). Cyclic stretch of vascular smooth muscle cells increased apoptosis of cells on collagen I, but not on other matrixes, and this effect was mediated by a pathway involving Rac, p38 MAP kinase, and p53 (40). Smooth muscle contraction was inhibited by brief pretreatment with RGD peptides that bind ␣ v ␤ 3 and ␣ 5 ␤ 1 integrins (47).…”
Section: Responses Of Cells To Externally Applied Strainmentioning
confidence: 98%
“…Classical studies of cellular responses to mechanical forces have demonstrated that fibroblasts, smooth muscle cells, and cardiac myocytes orient in response to cyclic stretch, although the direction of alignment can be either parallel or perpendicular to the direction of stretch depending on the cell type (3, 4). Externally applied strain also influences cell growth and survival (4,39,40). In all of the in vitro systems, forces are by definition transmitted through cell contacts with the substratum, thereby implicating integrins in mechanotransduction.…”
Section: Responses Of Cells To Externally Applied Strainmentioning
confidence: 99%
“…The role played by SMCs in vascular complications has been widely investigated, with research focusing on mechanical stimuli, (ECM) protein adhesion and cell behaviour [11][12][13][14]. In particular, the SMCs ability to proliferate and produce HA has been closely examined.…”
Section: Introductionmentioning
confidence: 99%